CHALLENGES IN THE MARKETING AND BRANDING OF CLUSTERS - Marita Koszarek (Polityki Europejskie, Finanse i Marketing)
Clusters have proved to be powerful engines of economic development in the European Union. Clusters and their stakeholders can derive many benefits from a strong cluster brand. However, they face numerous branding and marketing challenges. Specifics of clusters, such as multiple stakeholders, make it difficult to forge a strong brand identity. This paper addresses the need to develop a cluster specific approach to branding and marketing. The aim of the study, on which this paper is based, was to analyse the current branding and marketing efforts of Polish cluster initiatives and identify the main challenges that come with branding and marketing of clusters. It is discussed how clusters can use branding and marketing for strategic development purposes. The cluster specific approach to marketing tools and channels is proposed. Furthermore, cluster policy actions, reflecting the outcomes of the study, are recommended.